2006
DOI: 10.1097/01.aids.0000238402.70379.d4
|View full text |Cite
|
Sign up to set email alerts
|

What is the relevance of mental health to HIV/AIDS care and treatment programs in developing countries? A systematic review

Abstract: The expansion of AIDS treatment initiatives in resource-poor settings provides an opportunity for integrating mental health care into these programs. This systematic review of the literature on HIV and mental illness in developing countries examines the mental health risk factors for HIV, mental health consequences of HIV, psychosocial interventions of relevance for HIV-infected and affected populations, and highlights the relevance of these data for HIV care and treatment programs. We reviewed seven studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
234
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(251 citation statements)
references
References 52 publications
8
234
0
9
Order By: Relevance
“…PHQ-2 ≥3 demonstrated high sensitivity (85%) and specificity (95%) for diagnosing any PHQ-9 depressive disorder (AUC, 0.97), and 91% and 77%, respectively, for diagnosing PHQ-9 MDD (AUC, 0.91). Psychometrics were also good within four gender/age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) subgroups.CONCLUSIONS: PHQ-9 and PHQ-2 appear valid/ reliable for assessing DSM-IV depressive disorders and depression severity among adults living with HIV/AIDS in western Kenya. …”
mentioning
confidence: 93%
See 2 more Smart Citations
“…PHQ-2 ≥3 demonstrated high sensitivity (85%) and specificity (95%) for diagnosing any PHQ-9 depressive disorder (AUC, 0.97), and 91% and 77%, respectively, for diagnosing PHQ-9 MDD (AUC, 0.91). Psychometrics were also good within four gender/age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) subgroups.CONCLUSIONS: PHQ-9 and PHQ-2 appear valid/ reliable for assessing DSM-IV depressive disorders and depression severity among adults living with HIV/AIDS in western Kenya. …”
mentioning
confidence: 93%
“…With one exception 15 , the sparse literature on depression among individuals living with HIV/AIDS in sub-Saharan Africa has shown elevated rates of depression relative to community samples 3,8,10,[16][17][18][19][20][21][22][23][24][25] , consistent with western countries [26][27][28][29] . Thus, there is an urgency to incorporating mental health into HIV/ AIDS treatment programs in sub-Saharan Africa, including western Kenya [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of studies of mental health problems of HIV infected people in developing countries, Collins et al (2006) also found a significantly higher prevalence of depressive symptoms among HIV positive people compared with controls. Feelings of anxiety and distress are a normal and arguably even a healthy response to a diagnosis of HIV.…”
Section: Mental Disorders and Hiv/aidsmentioning
confidence: 97%
“…Previous systematic reviews have examined HIV risk behaviours among adults with severe mental illness (Meade and Sikkema 2005); the link between mistreatment in childhood disorders, mental health disorders, and HIV infection (Spies et al 2012); and literature on HIV and mental illness in low income countries (Collins et al 2006). Studies have also reviewed intervention trials to improve mental health among PLHIVs in LMICs (Sikkema et al 2015); as well as interventions using specific approaches like cognitive-behavioural therapy (Crepaz et al 2008) or that target specific disorders such as depression (Sherr et al 2011), anxiety ) and suicidality among PLHIV.…”
Section: Introductionmentioning
confidence: 99%